Comparison of Development of Non-governmental Organizations and the Current State of Their Funding in Slovakia and Austria - Mária Svidroňová; Gabriela Vaceková (Review of Economic Perspectives, 2014)
Non-governmental organizations play a vital role in the economy of every country. They are not only providers of special type of services that public sector is not capable of providing in full quality and quantity, and private sector is not interested in, but they are also watch dogs of the society and builders of active citizenship. Thus they have become an object of many research studies. The divergence in their goals, sizes, roles, types of services provided, and ways of funding make NGOs an interesting subject. As a goal for our research we therefore chose a comparison of the development and state of the Slovak and Austrian non-profit sector in the view of historical development of both countries. Consequently, we want to evaluate the funding of NGOs in Slovakia and Austria. In the paper we map the development of non-profit sector in Slovakia and Austria and in the context of a common historical development we assess a current state and a potential of economic strength of NGOs in both countries. The output is comparison of funding of NGOs in Slovakia and Austria based on statistical data evaluation. Subsequently, we propose recommendation for suitable diversification of the funding sources.
Keywords: 330